PENGARUH TEMPERATUR TEMPERING TERHADAP ENERGI IMPAK DAN POLA PATAHAN PADA BAJA AISI 1045 - Supriadi, Harnowo; Primartin, Abbit; Zulhanif, Zulhanif; Suudi, Ahmad (Universitas Muhammadiyah Metro, 2024)
The study of the effect of low temperature quenching cooling media on the value of toughness and types of fractures in AISI 1045 steel aims to determine the mechanical properties of increasing the value of toughness and ductility in steel. AISI 1045 steel is heated at a temperature of 850°C held for 60 minutes and then quenched quickly to a low temperature. The medium used is water. This tempering process can increase the impact energy. The impac energy value obtained at a temperature of 350°C is 18,33 Joule. Then at a temperature of 450°C it increases by 80 Joule, after that it increases again at a temperature of 550°C which is 121,33 Joule, the value increases higher at a tempering temperature of 650°C by 135,67 Joule. Observation of the type of fault shows that the higher the temperature the more ductile it can be seen from the results of the uneven and fibrous surface. Impact energy is influenced by variations in tempering temperature. When the tempering temperature is increased, the impact energi also increase. Keywords: AISI 1045 Steel, Quenching, Tempering, Impact Energy, Types of Fractures